Enhancing SME Performance Through Microfinance: Insights from Rural Nepal - Singh Thapa, Bharat; Pandey, Neema; Datt Pathak, Durga (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: The primary objective of this paper is to examine the effect of microfinance services on the performance of small and medium enterprises (SMEs) involved in microfinance programs in the Rupandehi district.Design/methodology/approach: A survey was conducted among 385 purposively chosen clients of Microfinance Institutions (MFIs) running SMEs using structured questionnaires incorporating demographic information and study variables. Data were analyzed using Structural equation modeling (SEM) through SmartPLS to investigate the effect of tailored microfinance services on selected performance indicators of SMEs.Findings: The research reveals positive and significant influences of microfinance services (measured by microloans, micro saving services, and skill development training) on the performance (measured by profit, sales growth, and employment creation) of SMEs. The findings emphasize the crucial role of integrated microfinance programs in enhancing SME profitability, employment, and sales growth.Conclusion: Microfinance services, especially micro-savings and training programs, significantly improve SME performance and sustainability by fostering employment, sales growth, and profitability by promoting skills development, financial stability, and efficient business practices.Implications: These findings present valuable insights for policymakers, microfinance practitioners, development partners, and SME owners seeking to enhance support mechanisms for the sustainability of small businesses. This paper contributessignificantly to academic literature, demonstrating the impact of microfinance services on financial performance and job creation using robust analytical methods to provide comprehensive insights.JEL Classification: G21, O16, O53, R11, P13